美国心脏学会/美国卒中学会卒中一级预防指南2024要点及解读 Interpretation of the Keypoints and Updates on 2024 Guideline for the Primary Prevention of Stroke: A Guideline from the American Heart Association/American Stroke Association - 戴丽叶1，姚婧璠2，张润华2，杨昕1，翟屹1，刘改芬2，姜勇1 (DAI Liye1, YAO Jingfan2, ZHANG Runhua2, YANG Xin1, ZHAI Yi1, LIU Gaifen2, JIANG Yong1 ) (Zhongguo cuzhong zazhi)
2024年，美国心脏学会和美国卒中学会发布了2024版卒中一级预防指南。该指南基于近10年最新的循证医学证据，提供针对无卒中病史人群的卒中预防策略。本文剖析该指南的关键推荐意见，结合卒中预防领域的最新研究成果，对相关文献进行解读，旨在清晰呈现最新的卒中筛查和预防建议，为公众和医务工作者提供实用的指导。 Abstract: In 2024, the American Heart Association and the American Stroke Association released the 2024 guideline for the primary prevention of stroke. Based on the latest evidence-based medical evidence in the past decade, this guideline provides stroke prevention strategies for people without a history of stroke. This article analyzes the key recommendations of this guideline, combines the latest research results in the field of stroke prevention, and interprets relevant literature, aiming to clearly present the latest suggestions on stroke screening and prevention, and provide practical guidance for the public and medical staff.